2021
DOI: 10.1136/bmjdrc-2021-002430
|View full text |Cite
|
Sign up to set email alerts
|

Cre/CysC ratio may predict muscle composition and is associated with glucose disposal ability and macrovascular disease in patients with type 2 diabetes

Abstract: IntroductionSince the ratio of creatinine to cystatin C (Cre/CysC) can reflect muscle volume, it has been proven to be a predictor of sarcopenia in patients with or without diabetes. Here, we investigated the predictive value of Cre/CysC for the skeletal muscle composition and its correlations with glucose disposal ability and diabetic complications in patients with type 2 diabetes.Research design and methodsThe skeletal muscle index (SMI) and mean skeletal muscle attenuation (MMA) values of 193 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
2
10
1
Order By: Relevance
“…It has been increasingly used in the screening of sarcopenia in diabetic and non-diabetic patients. Our previous studies have shown that the Cre/CysC can predict not only the muscle mass but also muscle density in patients with T2DM (24). Based on the close correlation between muscle and bone health, we further confirmed that Cre/CysC could be used as an independent predictor of BMD in the LS, FN, and TH.…”
Section: Discussionsupporting
confidence: 80%
“…It has been increasingly used in the screening of sarcopenia in diabetic and non-diabetic patients. Our previous studies have shown that the Cre/CysC can predict not only the muscle mass but also muscle density in patients with T2DM (24). Based on the close correlation between muscle and bone health, we further confirmed that Cre/CysC could be used as an independent predictor of BMD in the LS, FN, and TH.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with our data, the correlations between the SI and skeletal muscle mass in previous reports were not high. The correlation coefficients in a study by Yang et al, who evaluated the correlations of the SI with the CT value and cross-sectional areas of muscles at the L3 level, were r = 0.378 and r = 0.375, 40 while that in a study by Hirai et al, who reported the correlations between the SI and the skeletal muscle mass using BIA, was r = 0.44. 41 Although we showed that the SI was a good predictor of postoperative functional outcome, given that there are not always correlations between the skeletal muscle mass and physical performance in older individuals, 42 the SI should be cautiously used as a surrogate maker for the evaluation of sarcopenia.…”
Section: Discussionmentioning
confidence: 91%
“…Our study demonstrated that both the peak GH and IGF-1 SDS are independent predictors of SMA in children and adolescents of short stature. SMA is a comprehensive marker that determines both SMI and FMI, and the GH/IGF-1 axis may regulate muscle density through complex mechanisms ( 48 , 49 ).…”
Section: Discussionmentioning
confidence: 99%